2018
DOI: 10.2478/hppj-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Resistance screening of lentil cultivars against the root-knot nematode Meloidogyne incognita

Abstract: SummaryThe root-knot nematode Meloidogyne incognita is a major soil parasite of lentil crops. Increasing restrictions of chemical nematicides have triggered a growing attention and interest in alternate root-knot nematode management. The present study was conducted to examine the level of resistance and/or susceptibility of fi ve lentil cultivars (PL-456, KLS-218, Desi, DPL-62, Malika), grown in pots, against the root-knot nematode M. incognita. Root-knot nematode reproduction and host damage were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
2
4
0
1
Order By: Relevance
“…Similarly, all tested cultivars showed reduction in plant yield due to nematode infestation. Similar results were also observed by other workers that resistant cultivars yield comparatively better than susceptible cultivars (Ansari et al, 2018). In addition to plant growth reduction, some biochemical changes were also found in all cultivar of tomato.…”
Section: Varietal Susceptibility and Disease Resistance Of Tomato Cul...supporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, all tested cultivars showed reduction in plant yield due to nematode infestation. Similar results were also observed by other workers that resistant cultivars yield comparatively better than susceptible cultivars (Ansari et al, 2018). In addition to plant growth reduction, some biochemical changes were also found in all cultivar of tomato.…”
Section: Varietal Susceptibility and Disease Resistance Of Tomato Cul...supporting
confidence: 90%
“…Because of the restrictions on chemical pesticide use and their adverse effects on the environment, as well as on human and animal health, therefore, alternative strategies for nematode management are highly desirable (Ntalli et al, 2020). Nematode infestation levels could be minimized in the soil by using resistant cultivars with crop rotation (Ansari et al, 2018). The use of resistant cultivars is an environmentally friendly, safe, most comfortable and economically feasible alternative strategy to manage root-knot nematodes (Sujatha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in total chlorophylls and total carotenoids were found least pronounced with 13.6% and 14.1%, respectively, in the Red Ace cultivar, which was statistically different from other susceptible cultivars (Table 4). A similar reduction in total chlorophyll and carotenoid content were also observed in the studies of Ansari et al (2018) and Tsaniklidis et al (2021) on lentil and Cucumis melo infested with M. incognita and M. javanica. The maximum damage caused to host plant resulted in physiological and biochemical changes caused by nematode feeding.…”
Section: Statistical Analysessupporting
confidence: 82%
“…Table 1 revealed that the final nematode population in 250 g soil was marked maximum in highly susceptible cultivar Red Express (2265) followed by susceptible cultivar Ruby Red (1928), moderately susceptible Red Queen (1664) and Atlas (1517), and moderately resistant cultivars DDR (847), Red Ace (816) and CG (766). These results are evident from work done previously by different researchers as they have investigated the reaction of different okra, carrot, tomato and lentil cultivars to root-knot nematodes (Mukhtar et al, 2014;Khan et al, 2018;Asif et al, 2018;Ansari et al, 2018) and reported varying levels of resistance or susceptibility. The population of nematodes in soil was significantly highest in highly susceptible and susceptible cultivars whereas it decreased in moderately resistant and resistant beetroot cultivars.…”
Section: Statistical Analysesmentioning
confidence: 63%
“…Bu çalışmada, nematod ile bulaşık bitkilerde belirlenen klorofil içeriği, nematod verilmeyen kontrol bitkilerinden daha düşük tespit edilmesine rağmen, bu azalış oranı önemli seviyede değildir. Benzer şekilde, Lopez-Gomez and Verdejo-Lucas ( 2017 (Ansari et al 2018, Belair and Boivin 1988, Korayem and Bondok Moawad 2013, Lopez-Gomez et al 2015, Mukhtar et al 2013. Bitki köklerinde kök-ur nematodlarının neden olduğu urlar, bu nematod cinsinin varlığını belirlemek için önemli bir simptomdur.…”
Section: Tartişma Ve Kaniunclassified